Effect of particle size on combustion of coconut shell in a bubbling fludized bed combustor (2012)
"Combustion characteristics of coconut shell (CS) samples in an experimental model bubbling fluidized bed combustor (BFBC) was investigated with special focus on effect of particle size of the CS CS waste obtained from farm were crushed and classified into three sizes; Size X (12-50mm), SizeY (2-l2mm) and Size Z (<2mm). For overbed feeding of the feedstock, the impact of the particle size on emission and combustion performance were examined. in a 150mm diameter experimental model BFBC. Throughout the investigation inert bed temperature was fixed to a constant value of 750°C by means of electronic based inert bed temperature regulating unit (ITRU). Results showed that CS particle size have pronounced impact on combustion characteristics and the pollutants emission from the BFBC. It was observed that the Pollutants' emission was within acceptable limits for Size Y at about 310ppm for CO, <200PPM for NOx and almost zero for SOx. The results indicate that CS could be used as combustion feedstock for environmentally energy generation in a BFBC. "